Perbandingan Kandungan Logam Berat di Air dan Sedimen Sungai Cimande, Provinsi Jawa Barat - Wardhani, Eka; Marganingrum, Dyah; Agustian, Didin; Sugihhartati, Rachmawati; Rohan, Prayudha (Jurnal Serambi Engineering, 2026)
Heavy metal pollution in river ecosystems has the potential to disrupt the environmental balance and endanger human health, thus requiring a study of metal content in water and sediment segments. This study aims to analyze the concentrations of cadmium (Cd), chromium (Cr), and copper (Cu) in river water and sediments and compare them with the quality standards set by Government Regulation No. 22 of 2021. Sampling was conducted purposively at several stations in the upper, middle, and lower reaches of the river, then analyzed using Atomic Absorption Spectrophotometry (AAS) after undergoing preparation and wet destruction processes. The results showed that the levels of Cd, Cr, and Cu in sediments were generally higher than in water, indicating the role of sediments as a medium for metal accumulation. At point 3, the concentration of Cu in the sediment exceeded the ISQC Low ANZECC threshold value of >65 mg/kg, while the Cr and Cu levels in the water exceeded the class 2 quality standards of >0.05 and >0.02 mg/L. Overall, the quality of river water and sediment is greatly influenced by industrial waste, thus requiring efforts to control sources of pollution and regular monitoring in the study area.